Increasing Legal Effectiveness in Cipasung Village, Lemahsugih District, Majalengka Regency, West Java - Belardo Prasetya Mega Jaya; Trixi Karinina Dewi Sindhutomo; Akbar Ari Rangga Prabu Zulkifar; Wilda Riva Fadhilah; Anabela Callista Zahwa; Firanda Bery Amini; Meutia Irdina Khairunnisa; Yoshi Daud Shimada; Christian Sandy Pangestu; Nasrul Hidayat; Chatri Pratiwi Ningrum (EQUATOR SINAR AKADEMIA, 2023)
One of the problems that occurred in Cipasung Village is regarding the legal awareness of the community and the resolution of disputes/conflicts between citizens was not resolved properly so that the law did not apply effectively. Therefore, the objectives of this study are to: (1) Explain and analyze the effectiveness of law in society; (2) Explain and analyze How the Implementation in increasing the effectiveness of law in Cipasung Village, Lemahsugih District, Majalengka Regency, West Java. The approach used in this study is a qualitative approach, with a descriptive method. The effectiveness of law in society is determined by various factors; legal factors, law enforcement factors, facilities factors, community legal awareness factor, and legal culture factor. The implementation of increasing the effectiveness of law in Cipasung Village is by carrying out several programs, namely the literacy room program, nature school, discussions with village officials and the community regarding law, purposes and functions of law, procedures & methods for solving legal problems, legal awareness, and legal culture. With these programs, it will increase public knowledge and legal awareness so that the law can be applied effectively inCipasung Village.